Metacognitive beliefs as psychological predictors of social functioning: An investigation with young people at risk of psychosis. (April 2018) - Bright, Measha; Parker, Sophie; French, Paul; Fowler, David; Gumley, Andrew; Morrison, Anthony P.; Birchwood, Max; Jones, Peter B.; Stewart, Suzanne L.K.; Wells, Adrian
Abstract: Poor social functioning has been found to be present in those at risk for psychosis. This study aimed to examine metacognitive beliefs as potential predictors of structured activity (measure of social functioning) in those with an At Risk Mental State (ARMS). Regression and correlation analyses were conducted. The sample included 109 young people. Age was found to be positively correlated to structured activity. Metacognitive beliefs concerning uncontrollability and danger of worry were found to negatively predict structured activity. This was after controlling for age, gender, treatment allocation, cognitive schemas, positive symptom severity, social anxiety, and depression. Metacognitive danger items were most important. Age was the only control variable found to be an independent predictor of structured activity in the regression model, despite negative bi-variate relationships with structured activity found across three cognitive schema subscales and social anxiety. This is the first study to find that higher negative metacognitive beliefs about uncontrollability and danger predict lower social functioning in an ARMS sample, and that the perception of thoughts being dangerous was of particular importance. Psychological interventions should consider targeting this metacognitive dimension to increase social functioning. Future longitudinal research is required to strengthen findings in this area. Highlights: Age is a positive predictor of structured activity. A single negative metacognitive belief negatively predicted structured activity. Dangerousness of thoughts was an important predictor of structured activity. More research is needed in this area and of a longitudinal nature.